2015
DOI: 10.1002/ccd.26254
|View full text |Cite
|
Sign up to set email alerts
|

Aortic iatrogenic perforation during transseptal puncture and successful occlusion with Amplatzer ductal occluder in a case of mitral paravalvular leak closure

Abstract: Complications of transseptal puncture are significant and potentially life threatening. Aortic perforation is one of these complications and it needs to be repaired immediately. We report the case of a 48-year-old female with a history of rheumatic mitral valve disease. She underwent three previous mitral valve replacements. Her last echocardiogram reported an anterolateral leak in the mitral prosthesis. Catheterization was performed. During the procedure, when attempting to perform transseptal puncture, cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…As cardiac tamponade may be a life‐threatening condition, urgent open‐heart surgery seems to be the most promising treatment option to close the atrial leakage. However, some cases have reported the use of percutaneous device occlusion to close aortic perforation or cardiac perforation during transseptal puncture 5–9 . What these cases have in common is leaving the transseptal sheath in place until an occluder passes through it rather than prematurely withdrawing it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cardiac tamponade may be a life‐threatening condition, urgent open‐heart surgery seems to be the most promising treatment option to close the atrial leakage. However, some cases have reported the use of percutaneous device occlusion to close aortic perforation or cardiac perforation during transseptal puncture 5–9 . What these cases have in common is leaving the transseptal sheath in place until an occluder passes through it rather than prematurely withdrawing it.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cases have reported the use of percutaneous device occlusion to close aortic perforation or cardiac perforation during transseptal puncture. [5][6][7][8][9] What these cases have in common is leaving the transseptal sheath in place until an occluder passes through it rather than prematurely withdrawing it. Based on the recommendations from the above literature, when we encountered the complication of free wall perforation at the coronary sinus, the first solution was to attempt percutaneous occlusion of the perforation with a ventricular septal occluder through the transseptal sheath.…”
Section: Left Atrial Appendage System For Embolic Protection In Patiementioning
confidence: 99%
“…[9] Mijangos-Vázquez et al also reported on a similar complication, which was dealt with by Amplatzer Duct Occluder I. [10] However, we used an Amplatzer Duct Occluder II device, which is a softer device, to avoid any potential interference with the aortic valve cusps. As the 8-Fr sheath (effectively at least 3-mm diameter perforation) that was passed into the aorta, to avoid ongoing residual leak, we selected a 6-mm diameter device.…”
Section: Discussionmentioning
confidence: 99%
“…Due to very limited experience with these devices for cardiac perforations, complications remain largely unknown but are likely to be rare. [10]…”
Section: Discussionmentioning
confidence: 99%
“…With inadvertent puncture of adjacent structures, if noted early and dilator/sheath advancement avoided, usually catastrophies may be averted. However, expanding the iatrogenic hole with sheath advancement could be potentially catastrophic [ 37 ]. Thromboembolic complications may well be prevented by adequate anticoagulation (discussed below) and meticulous aspiration and flushing routine during the procedures, especially when exchanging wires and/or catheters; de-airing is also very important in order to avoid air embolism.…”
Section: Discussionmentioning
confidence: 99%